Surgical treatment of a patient with a comminuted fracture of the scapula (clinical observations) - A. A. Prokhorov; S. V. Novikov; N. N. Karchebnyy; A. N. Mironov; M. A. Panin; A. S. Petrosyan; V. E. Dubrov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Introduction. A comminuted fracture of the scapula with displacement of bone fragments can cause the development of severe post-traumatic deformation with persistent loss of function of the upper limb. Objective – to present the results of surgical treatment of three patients with various fractures of the scapula. Materials and methods. The analysis of surgical treatment of 3 patients of working age with comminuted fractures of the scapula with a dubious prognosis for the restoration of the function of the upper limb in the case of choosing a conservative treatment strategy was performed. After a preliminary analysis of the computed tomography data, the surgical technique protocol and the choice of implants were determined. Surgical treatment was carried out in the early post-traumatic period. The early postoperative period was uneventful and without complications in all cases. The follow-up period after surgery ranged from 6 weeks to 6 months. Results. In all 3 cases, X-ray consolidation of fractures was noted, the return of the full function of the upper limb. The median on the DASH questionnaire was 11.7 points. Conclusion. Based on the results of the proposed observations, it seems appropriate to evaluate the positive clinical, functional (complete recovery of the function of the upper limb) and radiological results (stable fixation, the process of fracture consolidation), despite a severe injury to the scapula, often leading to a permanent loss of working capacity and significantly limiting normal daily activities.